Smooth talking stranger - Kleypas, Lisa. (New York : St. Martin's Paperbacks, 2010)
Jack Travis leads the uncomplicated life of a millionaire Texas playboy. He makes no commitments, he loves many women, he lives for pleasure. Until one day, a woman appears on his doorstep with fury on her face and a baby in her arms. It seems Jack is the father and this woman is the baby's aunt.
Keywords: Millionaires -- Texas -- Fiction; Abandoned children -- Fiction; Birthfathers -- Fiction; Love stories